1998
DOI: 10.1038/sj.onc.1201881
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PTEN/MMAC1 alterations in uncultured melanomas and melanoma cell lines

Abstract: A novel tumor suppressor gene, PTEN/MMAC1, has been recently shown to be mutated in gliomas, breast, prostate, kidney cancers and melanomas. Loss-ofheterozygosity studies in melanoma have suggested the presence of at least one chromosome 10q locus lost early in tumor progression. In this study, we screened 45 melanoma cell lines and 17 paired uncultured metastatic melanoma and peripheral blood specimens for PTEN/ MMAC1 alterations using PCR-SSCP and direct sequencing. We found nine melanoma cell lines with hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
299
3
7

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(319 citation statements)
references
References 18 publications
10
299
3
7
Order By: Relevance
“…Recently, germline mutations in the SMAD4/DPC4 gene were found in a subset of familial and sporadic juvenile polyposis cases (Howe et al, 1998), and the PTEN/MMAC1 gene have been implicated as the predisposing factor in Cowden disease . Somatic PTEN/ MMAC1 mutations have also been found in a variety of human cancers Teng et al, 1997), and we and others have recently shown that 30 ± 40% of melanoma cell lines harbour PTEN/MMAC1 deletions or mutations (Guldberg et al, 1997;Tsao et al, 1998). Although the exact functions of LKB1/STK11 and PTEN/MMAC1 in the regulation of cell growth and di erentiation remain to be elucidated, one appealing hypothesis would be that aberrations of LKB1/STK11 and PTEN/MMAC1 could confer similar phenotypic changes to melanocytes.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Recently, germline mutations in the SMAD4/DPC4 gene were found in a subset of familial and sporadic juvenile polyposis cases (Howe et al, 1998), and the PTEN/MMAC1 gene have been implicated as the predisposing factor in Cowden disease . Somatic PTEN/ MMAC1 mutations have also been found in a variety of human cancers Teng et al, 1997), and we and others have recently shown that 30 ± 40% of melanoma cell lines harbour PTEN/MMAC1 deletions or mutations (Guldberg et al, 1997;Tsao et al, 1998). Although the exact functions of LKB1/STK11 and PTEN/MMAC1 in the regulation of cell growth and di erentiation remain to be elucidated, one appealing hypothesis would be that aberrations of LKB1/STK11 and PTEN/MMAC1 could confer similar phenotypic changes to melanocytes.…”
mentioning
confidence: 65%
“…The most commonly altered targets identi®ed thus far include chromosome arms 1q, 6q, 9p, 10q and 11q (Albino, 1995;Welch and Goldberg, 1997). Recently, alterations of the tumour suppressor genes p16 INK4/CDKN2 and PTEN/MMAC1 on 9p and 10q, respectively, have been demonstrated in signi®cant proportions of melanoma lesions and cell lines (Kamb et al, 1994;Bartkova et al, 1996;Castellano et al, 1997;Guldberg et al, 1997;Walker et al, 1998;Tsao et al, 1998), and the AIM1 gene has been suggested as a good candidate for the putative tumour suppressor on chromosome 6 (Ray et al, 1997).…”
mentioning
confidence: 99%
“…As this tumour suppressor gene is located at chromosome 10q23.3 and melanomas frequently harbour deletions at chromosome 10q22-qter (Isshiki et al, 1993;Herbst et al, 1994;Walker et al, 1995;Healy et al, 1996Healy et al, , 1998 like carcinomas of the prostate (Trybus et al, 1996) and the kidney (Speicher et al, 1994), inactivation of PTEN/MMAC1 has been supposed to occur in melanomas. Actually, deletions and mutations of PTEN/MMAC1 have been found in 29 -43% of investigated melanoma cell lines (Guldberg et al, 1997;Tsao et al, 1998;. We therefore tested melanoma primary resection specimens for mRNA and protein expression and PTEN/MMAC1 cDNAs for the presence of mutations or deletions.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions and mutations of PTEN/MMAC1 have been reported in a wide variety of human cancers, including tumours of the brain, the lung, the prostate and the breast Bonneau and Longy, 2000;di Cristofano and Pandolfino, 2000), placing this gene among the most commonly mutated genes in human cancer. In melanoma cell lines, inactivating deletions or mutations of PTEN have been reported in 29 -43% (Guldberg et al, 1997;Tsao et al, 1998Tsao et al, , 2000. We therefore looked for PTEN/MMAC1 alterations in melanoma resection specimens at mRNA and protein level by semiquantitative RT -PCR, sequencing of cDNA transcripts and immunohistochemistry.…”
mentioning
confidence: 99%
“…Although germline heterozygous mutations of PTEN do not confer a melanoma phenotype, they do lead to a cancer-prone state in the mouse (DiCristofano et al, 1998;Stambolic et al, 1998;Podsypanina et al, 1999). Furthermore, allelic loss or mutation of PTEN have been described in uncultured melanoma specimens, metastasis as well as established melanoma cell lines (Guldberg et al, 1997;Teng et al, 1997;Tsao et al, 1998). In addition, re-introduction of PTEN into PTEN-de®cient melanoma cells has been shown to suppress growth (Robertson and Jones, 1998).…”
Section: Rtk-ras-mapk Pathway In Pathogenesis Of Melanomasmentioning
confidence: 99%